Nap Opportunity As a Strategy to Improve Short-Term Repetitive Maximal Performance During the 5-m Shuttle Run Test: A Brief Review - Chtourou, Hamdi; H'mida, Cyrine; Boukhris, Omar; Trabelsi, Khaled; Ammar, Achraf; Souissi, Nizar (International Journal of Sport Studies for Health, 2019)
Sleep is fundamental for recovery and good mental, cognitive and physical performance. Many factors could affect the sleep of the physical active people or athletes such as: late night training sessions or competition, Ramadan fasting and jetlag. These conditions that affect the sleep quality have significant negative effects on mental, cognitive and physical performance. Thus, scientists have to find strategies to overcome the perturbation of sleep and to optimize mental, cognitive and physical performance especially for physical active people and athletes. One of the proposed strategies is the nap opportunity. Otherwise, in their routinely training sessions, athletes are required to perform short-term repetitive maximal sprints. One of the utilized exercise for testing or training is the 5-m shuttle run test (5mSRT). Recent studies concluded that a nap opportunity has a positive effect on performance during the 5mSRT. These studies reported that this positive effect depends on the duration and the time of day of the nap opportunity. Indeed, the positive effect of the nap opportunity was better after a duration of 45-minutes compared to a 25-minutes. Also, this positive effect was reported when the nap opportunity was performed at 14h00 or 15h00. However, no-positive effect was reported when the nap opportunity was realized at 13h00.